2006
DOI: 10.1016/j.ejheart.2006.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary regurgitation and right ventricular dysfunction on oxygen uptake recovery kinetics in repaired tetralogy of Fallot

Abstract: In ToF patients, severe PR and RV dysfunction lead to delayed recovery from exercise. CPX can identify patients with severe PR and RV dysfunction and may be useful to guide the pulmonary valve replacement decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…18 Despite the fact that patient symptoms improved significantly in this cohort as previously reported (85% of patients were NYHA Class II-IV pre-TPVI vs. 15% post-TPVI), 13 patients in the current study showed no change in peak VO 2 , VO 2 at AT, or RER after TPVI. This is in line with previous studies that showed similar findings.…”
Section: Discussioncontrasting
confidence: 48%
“…18 Despite the fact that patient symptoms improved significantly in this cohort as previously reported (85% of patients were NYHA Class II-IV pre-TPVI vs. 15% post-TPVI), 13 patients in the current study showed no change in peak VO 2 , VO 2 at AT, or RER after TPVI. This is in line with previous studies that showed similar findings.…”
Section: Discussioncontrasting
confidence: 48%
“…In response to the regurgitated volume, the RV dilates to overcome the increased loading conditions (1,16). Long-standing PR will eventually lead to dysfunction of the RV, and patients may experience reduced exercise tolerance (17). In such cases, PVR with a competent pulmonary valve provides a satisfactory solution, with excellent short-term results in terms of ventricular function and NYHA functional class (4,18).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, several authors have shown that the kinetics of VO 2 recovery both after the constant-power and the incremental exercise testing are slowed in patients with congenital heart disease and CHF [19,[66][67][68][69]; data for postmyocardial infarction patients are less clear [70,71].…”
Section: Vo 2 Off-kineticsmentioning
confidence: 98%